Using a mixture of local bone dust and morselized bone as graft materials in single- and double-level ACDF - Ma, Fei; Xu, Shicai; Liao, Yehui; Tang, Qiang; Tang, Chao; Wang, Qing; Zhong, Dejun (BMC musculoskeletal disorders, 2021)
Background Using a cage filled with local bone in anterior cervical discectomy and fusion (ACDF) can eliminate morbidities associated with autograft harvest from the iliac crest while achieving high fusion rates. However, there is still no consensus regarding the methods for using local bone grafts. This retrospective study was performed to compare the clinical and radiological outcomes of using a mixture of bone dust and morselized bone versus morselized bone alone in ACDF. Methods A retrospective study of 228 patients affected by cervical degenerative disease who had undergone single- or double-level ACDF between January 2014 and June 2018 was performed. Nanohydroxyapatite/polyamide-66 (n-HA/PA66) combined with morselized bone was used in 111 patients (group A: single-level ACDF in 51 patients and double-level ACDF in 60 patients), whereas the n-HA/PA66 cage combined with a mixture of bone dust and morselized bone was used in 117 patients (group B: single-level ACDF in 58 patients and double-level ACDF in 59 patients). The fusion rate, extent of cage subsidence, fusion segmental height (FSH), C2-7 lordosis, segmental sagittal alignment (SSA), 10-point visual analog scale (VAS) score, and Neck Disability Index (NDI) were compared between the two groups. Results The VAS score and NDI were significantly reduced after the operation in group A and group B. At the final follow-up, the fusion rate was 90.2 % (46/51) and 94.8 % (55/58) in patients treated with single-level ACDF in group A and group B, respectively (p > 0.05). In patients treated with double-level ACDF, bone fusion was achieved in 52 patients (86.7 %) in group A and 55 patients (93.2 %) in group B (p > 0.05). The fusion rate of single- and double-level ACDF was higher in patients in group B than those in group A at the 3-month, 6-month and 12-month follow-ups (p < 0.05). The extent of cage subsidence after single- and double-level ACDF was lower in patients in group B (1.5 [+ or -] 0.5 mm and 2.3 [+ or -] 0.8 mm, respectively) than in those in group A (1.8 [+ or -] 0.7 mm and 2.9 [+ or -] 1.4 mm, respectively) (p < 0.05). There was no significant difference between the two groups in the C2-7 lordosis, FSH, SSA, VAS score, or NDI before or after the operation (p > 0.05). Conclusions Using a mixture of local bone dust and morselized bone as cage-filling materials yielded comparably good clinical outcomes as using morselized bone alone in single- and double-level ACDF. However, the mixture graft of bone dust and morselized bone was more beneficial in promoting early fusion and reducing cage subsidence. Keywords: Anterior cervical discectomy and fusion, Bone dust, Morselized bone, Graft materials, Surgery